A double-masked, sham-controlled trial of rose bengal photodynamic therapy for the treatment of fungal and acanthamoeba keratitis: Rose Bengal Electromagnetic Activation with Green Light for Infection Reduction (REAGIR) study - NV Prajna; P Lalitha; S Sharma; D de Freitas; A Höfling-Lima; N Varnado; S Abdelrahman; V Cavallino; BF Arnold; TM Lietman; J Rose-Nussbaumer (Trials, 2024)
Abstract Background Infectious keratitis secondary to fungus or acanthamoeba often has a poor outcome despite receiving the best available medical therapy. In vitro rose bengal photodynamic therapy (RB-PDT) appears to be effective against fungal and acanthamoeba isolates (Atalay HT et al., Curr Eye Res 43:1322–5, 2018, Arboleda A et al. Am J Ophthalmol 158:64-70, 2014). In one published series, RB-PDT reduced the need for therapeutic penetrating keratoplasty in severe bacterial, fungal, and acanthamoeba keratitis not responsive to medical therapy. Methods This international, randomized, sham and placebo controlled 2-arm clinical trial randomizes patients with smear positive fungal and acanthamoeba and smear negative corneal ulcers in a 1:1 fashion to one of two treatment arms: 1) topical antimicrobial plus sham RB-PDT or 2) topical antimicrobial plus RB-PDT. Discussion We anticipate that RB-PDT will improve best spectacle-corrected visual acuity and also reduce complications such as corneal perforation and the need for therapeutic penetrating keratoplasty. This study will comply with the NIH Data Sharing Policy and Policy on the Dissemination of NIH-Funded Clinical Trial Information and the Clinical Trials Registration and Results Information Submission rule. Our results will be disseminated via ClinicalTrials.gov website, meetings, and journal publications. Our data will also be available upon reasonable request. Trial registration NCT, NCT05110001 , Registered on November 5, 2021.